2016
DOI: 10.1177/1420326x16672277
|View full text |Cite
|
Sign up to set email alerts
|

Radon equilibrium factor and perceived air quality in an air-conditioned auditorium in Lublin, Poland

Abstract: The study reports measurements of radon and its decay products and of perceived air quality carried out in an occupied and unoccupied auditorium at the Lublin University of Technology in Lublin, Poland during three air conditioning system operation modes – air conditioning off, air conditioning on and air conditioning on/off. In the air conditioning on/off mode radon and its decay product concentrations and values of perceived air quality were inversely related. During that air conditioning operation mode, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…(b) Larger variations were observed for radon equilibrium factor (F = 0.04 to 0.97) in Bangladeshi dwellings. Several studies (Chen & Harley, 2018a, 2018bHarley et al, 2012;Iimoto, 2000;Kranrod et al, 2009;Nader, 2019;Polednik et al, 2018;Yasuoka et al, 2009) clarified the following parameters as the influential to the variation indoor F: dwelling structure, human lifestyle, room occupancy, and usage of mechanical ventilation appliances. Thus, these parameters should also be focused on in systematic radon research for Bangladeshi dwellings in order to explain the sources of observed large variation in indoor F across the country.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…(b) Larger variations were observed for radon equilibrium factor (F = 0.04 to 0.97) in Bangladeshi dwellings. Several studies (Chen & Harley, 2018a, 2018bHarley et al, 2012;Iimoto, 2000;Kranrod et al, 2009;Nader, 2019;Polednik et al, 2018;Yasuoka et al, 2009) clarified the following parameters as the influential to the variation indoor F: dwelling structure, human lifestyle, room occupancy, and usage of mechanical ventilation appliances. Thus, these parameters should also be focused on in systematic radon research for Bangladeshi dwellings in order to explain the sources of observed large variation in indoor F across the country.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Although pre-calculated equilibrium factors and dose conversion factors from epidemiological models are commonly used in dose assessment for simplicity and practicality, these values may differ from the actual values present in the investigated environment [ 14 ]. Various environmental conditions can influence the radon equilibrium factor, which represents the ratio of the concentrations of short-lived radon progeny to the concentration of radon gas.…”
Section: Introductionmentioning
confidence: 99%